The Galactic Bulge Exploration. VI. Gaia Enceladus/Sausage RR Lyrae Stars in the Inner-central Stellar Halo of the Milky Way - Andrea Kunder; Zdenek Prudil; Antonela Monachesi; Samuel J. Morris; Kathryn Devine; Joanne Hughes; Kevin R. Covey; R. Michael Rich; Elisa A. Tau (The Astronomical Journal)
We present a view of the stellar halo in the inner-central regions of the Milky Way ( R ≲ 10 kpc) mapped by RR Lyrae stars. The combined BRAVA-RR/APOGEE RR Lyrae catalog is used to obtain a sample of 281 RR Lyrae stars located in the bulge region of the Galaxy, but with orbits indicating they belong to the inner-central halo. The RR Lyrae stars in the halo are more metal-poor than the bulge RR Lyrae stars and have pulsation properties more consistent with an accreted population. We use the Milky Way-like zoom-in cosmological simulation Auriga to compare the properties of the RR Lyrae stars to those expected from the “Gaia-Enceladus-Sausage” (GES) merger. The integrals of motions and eccentricities of the RR Lyrae stars are consistent with a small fraction of 6–9% ± 2% of the inner-central halo RR Lyrae population having originated from GES. This fraction, lower than what is seen in the solar neighborhood, is consistent with trends seen in the Auriga simulation, where a GES-like merger would have a decreasing fraction of GES stars at small Galactocentric radii compared to other accreted populations. Very few of the Auriga inner Galaxy GES-18 particles have properties consistent with belonging to a bulge population with ( z _max < 1.1 kpc), indicating that no (or very few) RR Lyrae stars with bulge orbits should have originated from GES.